The Contractionary Short-Run Effects of Nominal Devaluation in Developing Countries: Some Neglected Nuances - Arslan Razmi (University of Massachusetts, Department of Economics, 2005)
This paper extends the model developed by Krugman and Taylor (1978) to take into account interesting features of the evolving structure of global trade. The growing presence of transnational production chains and differential pricing behaviour of exports destined for industrial and developing countries are accommodated. Individual country and panel data pass-through estimates derived from several econometric approaches are provided to justify the latter extension. The likelihood of contractionary short-run effects of devaluations is shown to be positively related to: (1) the proportion of a country's exports destined for other developing countries, and (2) the presence of TNCs in either the export or home goods-producing sector. Unlike the Krugman-Taylor case, devaluation will generally have a contractionary impact even if: (1) trade is initially balanced, (2) consumption behaviour does not differ between wage and profit earners, and (3) the government sector has a high marginal propensity to consume in the short-run. The resulting policy implications underline the need to take into account these increasingly important nuances of international trade while designing exchange rate policies for developing countries. JEL Categories: F12, F14, F23, F41
Keywords: 330; Differential pass-through elasticities; contractionary devaluations; transnational corporations; error correction models; autoregressive distributed lag models; structuralist models